Dealing with Dilemma’s: How Can Experiments Contribute to a More Sustainable Mobility System? - Bruijne, Mark de; Riet, Odette van de; Haan, Alexander de; Koppenjan, Joop (European Journal of Transport and Infrastructure Research, 2010)
Sustainable mobility has proved to be a perennial challenge to realize. Scholars have argued that experiments could point the way forward towards sustainable mobility (cf. Loorbach, 2007, Markard and Truffer, 2008). In doing so, literature attributes a vital but complex task to those who engage in experiments. However, an important knowledge gap pertains to whether and how experiments contribute to learning about transitions and in what way they should be managed to break-up the more or less inertial mobility governance system. This paper aims to analyze how state-of-the-art literature on the governance of multi-actor systems considers experiments to contribute to transitions and highlight key dilemma’s that professionals engaged in the management of experimental face in the day-to-day management and decision making processes during the experiment. The paper will highlight these dilemmas and choices and illustrate their importance for experiments in the field of transportation and more specifically in the specific context of the Dutch mobility system and the TRANSUMO research program. Identifying these dilemma’s benefits practitioners who are engaged in the management of experiments to more consciously reflect on and include issues of second-order learning in the day-to-day management and decision making during the experiment to reach a more sustainable mobile system.